Duodenal Stricture due to Necrotizing Pancreatitis following Endoscopic Ultrasound-Guided Ethanol Ablation of a Pancreatic Cyst: A Case Report - Chun, Jung Won (Clin Endosc, 2019)
The frequency of incidental detection of pancreatic cystic lesions (PCLs) is increasing because of the frequent use of cross-sectional imaging. The appropriate treatment for PCLs is challenging, and endoscopic ultrasound-guided ablation for PCLs has been reported in several studies. Although the feasibility and efficacy of this therapeutic modality have been shown, the safety issues associated with the procedure are still a concern. We present a case of a 61-year-old man who underwent ultrasound-guided ethanol ablation for PCL and needed repeated endoscopic balloon dilatation for severe duodenal stricture caused by necrotizing pancreatitis after the cyst ablation therapy.